High Value Conversion Technology of Nickel in Waste Electrolytes of Nitrogen Trifluoride by Electrolysis - Yongzhuan Ren; Yuxuan Ran; Jiaqi Yang; Yonggang Wei (Separations, 2023)
The method of precipitation treatment of high-nickel waste electrolytic slag was studied, coupled with multi-step treatment to improve the recovery rate of nickel. In this study, HNO3 was used as dissolving agent, NaOH and Na2CO3 as precipitating agents, and the waste electrolytic slag was dissolved in the liquid phase and then precipitated. The results show that the electroslag with high nickel content can be completely dissolved under the optimal solid-liquid ratio of 1:10. When the pH of the leaching solution was adjusted to 7.5 by 5% NaOH solution, the iron removal rate could reach 99.3%. When the pH was adjusted to 11 with 5% Na2CO3, the nickel could be completely precipitated after standing, and the main component was basic nickel carbonate. The further recovery experiments show that high purity NiO can be obtained after the basic nickel carbonate is oxidized and calcined, and the average recovery rate of nickel is 92.4%. This study is of great practical significance to improve the treatment efficiency of the chemical precipitation method, reduce the operating cost of the chemical precipitation method, and reduce the production of secondary pollutants in the process of nickel recycling.